Primeros casos clínicos de infecciones por Klebsiella pneumoniae productora de OXA-48 en Perú - Silva Caso, Wilmer Gianfranco (2021)
Background:Carbapenemase-producing Enterobacteriaceae(CPE) represents a global public health concern and systemic infections associated with OXA-48 carbapenemase are in creasingly being reported in Latin America. Here, we present the first 2 cases of systemic infections by OXA-48-Producing Klebsiellapneumoniae in Peru. A favor able clinical response was observed after targeted treatment with colistin as a backbone.